KAJIAN DESAIN PENGEMBANGAN EKONOMI KREATIF BERDASARKAN POTENSI WILAYAH PERDESAAN - Ali Salmande; Agus Lukman Hakim; M. Robbi Qawi; Miftah Faiz Ali Ramdhani (Jurnal Bina Bangsa Ekonomika, 2023)
The purpose of this study is to examine the design of creative economic development based on the potential of rural areas. This research method is a qualitative and quantitative descriptive method. This research was conducted in Serang Regency, Banten Province, with a study focused on the pattern design of creative economic development in Serang Regency. This research used two data sources, namely primary data sources and secondary data sources. Based on a survey of 2 regional clusters in Serang Regency, culinary 41.07 percent, craft 17.86 percent, fashion 14.29 percent, and architecture 12.50 percent. Based on the number of workers 48.21 percent, Based on the length of business, Business actors who have been running a business around 4-10 years 55.36 percent, less than 3 years 30.95 percent, 11-20 years 9.52 percent and more than 20 year 4.17 percent. The government and the creative economy community in Serang Regency are expected to work together to improve creative economy training. Because there are still many creative economy entrepreneurs who have never attended coaching/training. The training needed by creative economy entrepreneurs is product marketing strategy, creative economic business financial management, innovative product design and business licensing mechanisms